Eskalasi dalam Proyek Multi Years - C. F. Maulidi (Seminar Nasional Insinyur Profesional (SNIP), 2021)
Escalation is the adjustment of the unit price of contract components which include labor, construction materials, energy and equipment to the contract value at the time of bidding. Escalation can be interpreted as a provision or reserve on the estimated cost intended to cover the increase in the price level due to time. The escalation component is obtained from the unit price of an item which is divided into labor, materials, and wages. The three components are used as a coefficient that will be calculated with the price index from the Central Statistics Agency. Escalation is a must for a contractor because price increases are something that cannot be controlled and will inevitably occur in accordance with inflation, but must be in accordance with the contract documents required for every construction work.